Методи вдосконалення управління кредитним портфелем банку в сучасних умовах - Степаненко, С. В.; Римар, О. Г.; Гулюк, О. І. (My University, 2021)
У статті доведено, що реалізація ефективних методів управління кредитним портфелем вимагає комплексного оцінювання його ефективності. Проведений огляд існуючих підходів до моделювання узагальненої оцінки кредитного портфелю дозволив визначити, що ключовими розглядаються критерії дохідності, ризикованості та ліквідності. Аналіз індикаторів оцінювання кредитного портфелю в контексті статистичного аналізу та економіко-математичного моделювання дозволив визначити основні показники, на яких має ґрунтуватися подібний аналіз: рівень кредитної активності окремо за суб’єктами господарювання та фізичними особами; рівень дохідності цих портфелів; рівень ризикованості; частка непрацюючих кредитів. В якості економіко-математичного інструментарію було використано кластерний аналіз, який дозволив сформувати групи банків за середніми значеннями досліджуваних показників. Відповідно кожному кластеру було запропоновано окремі шляхи підвищення ефективності кредитного портфелю. The important role of the banking system in the national economy is due to its function as a major intermediary in the redistribution of free financial resources between entities to improve the efficiency of their allocation and use of these resources. The unfavorable situation in the national banking system since 2014 requires a thorough review of the management of banking portfolios, including credit. The complexity of managing the loan banking portfolio is due to the diversity of its components, the dynamics of the external environment, the phase of the economic cycle and the general market situation, where the priority should be considered the level of solvency of individuals and businesses. The purpose of the article is to analyze the effectiveness of credit portfolio management of domestic banking institutions in the current conditions of financial development and on its basis to propose appropriate management tools. It is determined that balanced loan portfolio management involves the distribution of risks in proportion to all types of banking activity, effective planning of the profitability of active operations, taking into account the value of liabilities and capitalization. It is proved that the implementation of effective methods of loan portfolio management requires a comprehensive assessment of its effectiveness. A review of existing approaches to modeling a generalized assessment of the loan portfolio revealed that the key criteria are considered to be profitability, risk and liquidity. The analysis of credit portfolio valuation indicators in the context of statistical analysis and economic-mathematical modeling allowed to determine the main indicators on which such an analysis should be based: the level of credit activity separately for businesses and individuals; the level of profitability of these portfolios; level of risk; share of non-performing loans. Cluster analysis was used as an economic and mathematical tool, which allowed to form groups of banks according to the average values of the studied indicators. The results of constructing a tree-like histogram made it possible to single out 7 clusters according to certain indicators. Accordingly, each cluster was offered separate ways to increase the efficiency of the loan portfolio.
Methods of improving the bank's loan portfolio management in modern conditions
Keywords: кредитний портфель; банк; дохідність; ризикованість та ліквідність; кластерний аналіз; loan portfolio; bank; profitability; riskiness and liquidity; cluster analysis